The role of emotional quotients and adversity quotients in career success - Zhao, Yuyang; Sang, Biao (Frontiers in Psychology, 2023)
Career success has been considered equally important for both personal and organizational development. The purpose of the current study was to examine how trait emotional quotient (EQ) and adversity quotient (AQ) contribute to individuals’ objective career success (job position) and subjective career success (organizational commitment). Participants included 256 Chinese adults who completed four measurements—the Self-Reported Emotional Intelligence Test, Resilience Scale, Grit Scale, and the Affective, Continuance, and Normative Commitment Scale—and provided demographic information. After validating the four scales used in this study, multiple regression analysis revealed that only one aspect of trait EQ (regulation of emotion) positively predicted one component of organizational commitment (affective commitment). AQ was measured on two dimensions: resilience and grit. Only consistency of interest (grit) positively predicted affective commitment. Perseverance of effort (grit) and acceptance of self and life (resilience) positively predicted normative commitment. Personal competence (resilience) positively predicted continuance commitment but negatively predicted normative commitment. Only acceptance of self and life (resilience) positively predicted job position. Overall, these findings demonstrate the specific influence of trait EQ and AQ on career success for organizational professionals who want to improve organizational productivity as well as individuals who want to achieve success at work.